Biochar application in the mercury ions adsorption from aqueous solutions - Daria Gąsior; Wilhelm Jan Tic (Economic and Environmental Studies (E&ES), 2016)
Biochar is the carbon-rich product produced by thermal decomposition of organic material in anaerobic conditions or under limited supply of oxygen. The removal of pollutants from water using biochar materials is a low cost, sustainable approach for providing pure water. The adsorption of mercury ions onto pyrolyzed chicken manure, sewage sludge and rye straw was studied and compared with the adsorption of mercury ions onto commercial activated carbons of various origins and grain size. The impact of pH, biochar adsorbents amount and phase contact time on the adsorption efficiency were investigated. Tested biochars were characterized by large, porous surface area and their adsorption potential was comparable with the activated carbons.
Keywords: Q53; Q20; 330; sustainable development; biochar; activated carbon; water treatment; contaminants removal; adsorption